ANTIMICROBIAL POTENTIAL OF MARINE PHOTOSYNTHETIC BACTERIA AND BIOPIGMENT EXTRACTS AGAINST AQUATIC PATHOGENS - Hersa Javayu Defitra; Ummi Mardhiah Batubara; Thamrin Thamrin (Asian Journal of Aquatic Sciences, 2025)
Potential of marine photosynthetic bacteria (MPB) and their biopigment extracts as antimicrobial agents against two major aquatic pathogens, Aeromonas hydrophila and Staphylococcus aureus. The research was conducted from February to April 2025. Six MPB isolates were cultured under laboratory conditions to induce pigment production. Biopigments, natural pigments produced by microorganisms, exhibit antimicrobial and antioxidant properties. Pigment extraction was performed using acetone and ether, followed by evaporation to obtain concentrated pigment extracts. The antimicrobial activity of both MPB suspensions and their biopigment extracts was tested using the disc diffusion method on Mueller-Hinton Agar (MHA) media. The results showed that the MPB suspensions produced no inhibition zones against either pathogen. In contrast, the biopigment extracts demonstrated weak antimicrobial activity, with inhibition zone diameters ranging from 1 to 4 mm, a classification of weak. However, the ability of biopigment extracts to inhibit bacterial growth, even at low levels, suggests the presence of bioactive compounds with potential antimicrobial activity. These findings suggest that MPB-derived biopigments may serve as a natural alternative in future antimicrobial development